Cogon Grass Mesoporous Silica Nanoparticles Loaded with Uncaria gambir Extract and Photosensitizer for Photothermal Induced Anti-MRSA Activity: Formula Optimization and In Silico Exploration - Mardiyanto; Sabrina, Tia; Alhafizh, M. Faris; Kota, Natacha Brigida; Ramadhona, Sheza Inayah; Valenia, Novella; Amrullah, M. Ammar; Zulda, Daghfal Rafataqwa; Marrisca, R.D. Nindi; Alisyahbana, Sutan Satya; Fadilah, Ade; Pratiwi, Aisyah; Fithri, Najma Annuria (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
In recent years antimicrobial resistance (AMR) has grown to become a massive concern for the global community due to their lack of successful prevention and low recovery rates. One of methods with high efficiency in reducing AMR is photodynamic and photothermal therapy (PDPT), due to their independency from chemical mechanism of antimicrobial efficacy. Mesoporous silica nanoparticle (MSN) is an excellent carrier for potential alternative for AMR including photosensitizers and natural based active ingredients. Herein, we explored the use of various sources as silica precursors as well as optimization based on method of fabrication and coating agent to stabilize and load the active ingredients. We additionally incorporated Uncaria gambir extract and phycocyanin to increase MSN antimicrobial effect and photosensitizing ability. Cogon grass-based MSN (CG-MSN) has yet to be explored extensively and in this research, we compared their characteristics to a more established precursors such as tetraethyl orthosilicate (TEOS) and sodium silicate. Based on the results obtained, cogon grass-based precursors produced the highest yield, with entrapment efficiency of Uncaria gambir and phycocyanin as high as 98%. Furthermore, CG-MSN produced one of the highest photothermal increase and adsorption rate comparable to that of TEOS. From in silico exploration Uncaria gambir contained Gambiriin and Roxburghin as two of the most active phytoconstituents that influenced its antimicrobial activity. Based on this research we were able to synthesize a new precursor of silica from natural based product, cogon grass, and incorporate it as carrier for phytocompounds in the management of AMR.